Data privacy in interoperability environments – a case study in the Portuguese healthcare sector - Lopes, Secundino (2016)
Data sharing between organizations through interoperability initiatives involving multiple information systems is fundamental to promote the collaboration and integration of services. However, in terms of data, the considerable increase in its exposure to additional risks, require a special attention to issues related to privacy of these data. For the Portuguese healthcare sector, where the sharing of health data is, nowadays, a reality at national level, data privacy is a central issue, which needs solutions according to the agreed level of interoperability between organizations. This context led the authors to study the factors with influence on data privacy in a context of interoperability, through a qualitative and interpretative research, based on the method of case study. This article presents the final results of the research that successfully identifies 10 subdomains of factors with influence on data privacy, which should be the basis for the development of a joint protection program, targeted at issues associated with data privacy.